Developing a new hydrate saturation calculation model for hydrate-bearing sediments. (15th July 2019) - Dong, Huaimin; Sun, Jianmeng; Zhu, Jinjiang; Liu, Lei; Lin, Zhenzhou; Golsanami, Naser; Cui, Likai; Yan, Weichao
Highlights: The correlation between saturation exponent and water saturation was explored. A novel method of calculating hydrate saturation by resistivity was developed. Variation of hydrate microscopic distribution in hydrate formation was investigated. The effect of hydrate microscopic distribution on resistivity index was studied. Abstract: This study incorporates X-ray computed tomography (CT) technology into the in-situ observation of the xenon hydrate formation process in sand sediments under excess gas conditions. While the scanning images were used to obtain microscopic distribution information of the hydrate, we implemented the finite element method (FEM) to calculate the resistivity of the hydrate-bearing samples obtained from scanning images. Consequently, it was observed that the resistivity index (RI) versus hydrate saturation (Sh ) data matched better with our new calculation model rather than the simple Archie formula fitting model (i.e. experimental fitting model). Besides, we calculated the resistivity versus the hydrate saturation curves based on digital rock models with idealized hydrate distributions. These distributions included adhesive type, cemented type and scattered type. Observation of microscopic distribution and simulation results indicated that the resistivity versus hydrate saturation exhibited certain differences for the three types of hydrate distributions. We also found that saturation exponent ( n ) is a function of the hydrate saturation (Sh ), which can be applied in the proposed new calculation model in order to calculate the resistivity versus hydrate saturation data. This suggests that the established model is a useful methodology for the purpose of saturation calculations and reservoir identification in hydrate-bearing sediments.